Comparative assessment of measured and modelled aircraft noise around Amsterdam Airport Schiphol. (April 2022) - Simons, Dick G.; Besnea, Irina; Mohammadloo, Tannaz H.; Melkert, Joris A.; Snellen, Mirjam
Abstract: The impressive growth of the aviation industry and the number of flights entail several environmental repercussions, such as increased aircraft noise emissions. With the worrying number of complaints from the communities around airports comes also the distrust in numerical models used for aircraft noise prediction. In this study, we compare the 'Dutch aircraft noise model' predictions to measured values from the NOise MOnitoring System (NOMOS) around Amsterdam Airport Schiphol between 2012 and 2018. While the model underestimates aircraft noise in 2012, the model prediction improved throughout the years. We observe a decreasing trend of measured aircraft-related L d e n values of 0.6 dB(A)/year (a total of 3.6 dB(A) over the investigation period), although the total number of flight movements increased during the observation time. We propose that a change in fleet mix, as well as the implementation of Noise Abatement Procedures at Schiphol Airport, fuelled this trend.